Force Sensors: Hybrid Mechanoresponsive Polymer Wires Under Force Activation (Adv. Mater. 12/2013). (18th March 2013) - Feng, Hongbin; Lu, Jin; Li, Jinghong; Tsow, Francis; Forzani, Erica; Tao, Nongjian
<x xml:space="preserve">Abstract</x> Force activation is triggered in a stretched polymer wire with color changes produced as the molecules undergo structural and conformational changes. Nongjian Tao, Jinghong Li, and co‐workers show on page 1729 that the hybrid mechanosensitive polymer wire can function as a micro‐ and nanoscale force sensor. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>